Конёк-Горбунок: [для младшего школьного возраста] / Петр Ершов ; худ. Ст. Ковалёв - Ершов Петр Павлович (Эксмо, 2011)
Экземпляры: СФ (20140411) / Инвентарный номер: 49673 / Цена: 282.20 / Сис.шифр: Р1мл / Авт.знак: Е 80 / ГРНТИ: 17.82 / ББК: 84(2Рос.Рус)1